MANAGERIAL EMOTIONAL INTELLIGENCE AND STRATEGIC MANAGEMENT ACCOUNTING PRACTICES OF PHARMACEUTICAL INDUSTRIAL GOODS COMPANIES IN KWARA STATE - Muhammed Lawal Subair; Ezekiel Aiyenijo Adigbole; Kolawole Abdulgafar Mohammed (Gusau Journal of Accounting and Finance, 2025)
In implementing strategic management accounting practices, insufficient attention to managers' emotional intelligence often leads to poorly aligned strategies and weakened organizational performance, especially in the pharmaceutical manufacturing sector where adaptability and collaboration are vital. Therefore, considering managers’ emotional intelligence is crucial for successful SMA implementation. This study investigated the influence of managerial emotional intelligence on strategic management accounting (SMA) practices in selected pharmaceutical industrial goods companies in Ilorin, Kwara State. The study used a survey research design and the population covered all the eight (8) pharmaceutical manufacturing firms in Ilorin metropolis, kwara state. All the pharmaceutical manufacturing firms in Ilorin metropolis were selected for the study, hence, a census study. Primary data used for the study were collected with the use of questionnaire administration to the cost accountants, management accountants, internal auditors, production managers, sales managers and finance directors of the studied firms. Data collected for the study were analyzed using both descriptive and inferential statistics ordered logistic regression. The findings of the study were: self-awareness has a positive significance impact on strategic management accounting practices, self-awareness, empathy, self-regulation and motivation have significance impact on SMA practices in the studied manufacturing firms, p-value greater than 0.001, while social skills does not have significance influence on SMA practices in the study with (?=0.78,p<0.007 ). Based on the findings, it is concluded that emotional intelligence as contingency factors has a substantial influence on the strategic management accounting practices in the selected firms. It is therefore recommended that enhancing emotional intelligence in managers, particularly through training in self-awareness, empathy, self-regulation, and motivation, can improve SMA practices and strategic decision-making. Furthermore, the pharmaceutical manufacturing firms should deeply seized the importance of integrating emotional intelligence development into managerial training programs to optimize SMA outcome.